The Use of SQ3R Technique to Improve Reading Ability at Tenth-Grade Students of MA Thohir Yasin - Pratama, M. Iskandar; Nazri, M. Adib; Arfah, Hajriana; Wati, Laila (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study aimed to determine the effectiveness of the SQ3R technique in improving the reading ability of tenth-grade students at MA Thohir Yasin, with a focus on measuring reading skills before and after the implementation of the technique. A pre-experimental design using one group pre-test and post-tests was used in this study. The sample of this study was the X2 class which consisted of 20 students. The Data were collected from students’ pre-tests and post-tests using a questionnaire. The data were analyzed by using SPSS version 22 for Windows. After submitting the data to a paired sample t-test, it was found that there was a significant difference in the mean score between the pre-test and the post-test, t(df=19) = -11,258 at p=0.000 which meant that the alternative hypothesis was accepted and the null hypothesis was rejected. Thus, technique SQ3R significantly improved the reading ability of tenth-grade students of MA Thohir Yasin. Based on the research findings, the SQ3R technique has been shown to considerably increase students' reading skills, therefore English teachers should incorporate this technique into their reading education.